(untitled) (Journal of Asian Development Studies, 2024)
The prompt development of blockchain technology can transform financial reporting in the banking sector by improving transparency, accuracy, and efficiency. This study examines the magnitude of blockchain technology adoption in financial reporting among commercial banks in Pakistan, testing the factors influencing this adoption. The current study opts for a quantitative survey to extend a broad understanding of the phenomenon. This study employs the Partial Least Squares Structural Equation Modeling (PLS-SEM); the study analyzes the associations between blockchain technology, perceived benefits, challenges, and the adoption of blockchain technology. The findings underscore the importance of increasing awareness and understanding of blockchain technology among financial professionals and highlight the need to address technological and regulatory challenges to facilitate adoption.